2021
DOI: 10.1016/j.ekir.2020.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Novel Nicotinamide Modified-Release Formulation in the Treatment of Refractory Hyperphosphatemia in Patients Receiving Hemodialysis—A Randomized Clinical Trial

Abstract: Introduction Despite widespread use of phosphate binders (PBs), phosphate control is insufficient in many hemodialysis patients. Preliminary clinical observations suggest that nicotinamide may act synergistically with PBs to improve phosphate control. Methods This multinational, randomized, double-blind, placebo-controlled study evaluated the efficacy and safety of nicotinamide modified release (NAMR) in combination with oral PB in a large cohort of hemodialysis patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…1,25‐dihydroxyvitamin D, which has been shown to upregulate intestinal NPT2b in preclinical models, 24,25,50 also increases phosphate absorption 11,51 and transporter‐mediated phosphate absorption 16 in ESRD patients, suggesting a role for NPT2b in human phosphate absorption. Nicotinamide therapy reduces hyperphosphatemia in patients on dialysis 52 . Preclinical studies indicate the effect of nicotinamides is through decreased NPT2b mediated transport, 20,53 providing additional evidence for an appreciable role of NPT2b in human phosphate absorption.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1,25‐dihydroxyvitamin D, which has been shown to upregulate intestinal NPT2b in preclinical models, 24,25,50 also increases phosphate absorption 11,51 and transporter‐mediated phosphate absorption 16 in ESRD patients, suggesting a role for NPT2b in human phosphate absorption. Nicotinamide therapy reduces hyperphosphatemia in patients on dialysis 52 . Preclinical studies indicate the effect of nicotinamides is through decreased NPT2b mediated transport, 20,53 providing additional evidence for an appreciable role of NPT2b in human phosphate absorption.…”
Section: Discussionmentioning
confidence: 98%
“…Nicotinamide therapy reduces hyperphosphatemia in patients on dialysis. 52 Preclinical studies indicate the effect of nicotinamides is through decreased NPT2b mediated transport, 20 , 53 providing additional evidence for an appreciable role of NPT2b in human phosphate absorption. Two NPT2b inhibitors that were reported to decrease phosphate absorption in preclinical models recently advanced to the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study that did not observe a decrease in serum phosphate levels, the COMBINE trial (NCT02258074), had a dropout rate of 25% in the NAM group due to pill burden and gastrointestinal symptoms [191]. In the NICOREN (NCT01011699) and NOPHOS trials, the majority of reported adverse events are also gastrointestinal upset, as well as thrombocytopenia, anemia and pruritus [193,194]. However, a meta-analysis of the efficacy and safety of NAM on phosphate metabolism in hemodialysis patients revealed that thrombocytopenia was the only significant adverse effect caused by NAM [195].…”
Section: Clinical Interventionsmentioning
confidence: 99%
“…The dose-limiting adverse effect of niacin is skin flushing, caused by an increase in the vasodilator prostacyclin. Additional adverse effects of niacin and NAM include pruritus, skin rash, gastrointestinal disturbances and thrombocytopaenia [ 18 , 19 ]. Liver cell damage has been observed at intakes of niacin as little as 750 mg/day [ 20 ].…”
Section: Clinical Use Of Vitamin B3mentioning
confidence: 99%
“…Vitamin B3 vitamers have been tested in clinical trials for the treatment of hyperphosphataemia in CKD ( Figure 3B and Table 1 ). In CKD, niacin [ 26 ] or NAM [ 18 , 19 , 30 ], either alone or in combination with other phosphate binders, reduced serum phosphate levels in most trials through inhibition of the expression of the intestinal phosphate transporter NaPi2b by poorly characterized mechanisms. The main metabolite of NAM, N-methyl-2-pyridone-5-carboxamide, may accumulate in haemodialysis patients [ 19 ].…”
Section: Vitamin B3 In Ckdmentioning
confidence: 99%